First Clinical Experience with the Innova versus the Protege EverFlex Self-Expanding Bare Metal Stents in Superficial Femoral Artery Occlusions - Gabrielli, Roberto; Rosati, Maria Sofia; Chiappa, Roberto; Millarelli, Massimiliano; Marcuccio, Luigi; Siani, Andrea; Caselli, Giovanni (The Thoracic and Cardiovascular Surgeon, 2015)
Background To evaluate outcomes of superficial femoral artery (SFA) stenting with Boston Scientific Innova stent system (Boston Scientific Corporation Place, Natick, Massachusetts, United States) compared with ev3 Protege stent system (Endovascular, Inc., Plymouth, Minnesota, United States) in terms of safety and effectiveness and to identify factors predictive of restenosis.Methods From March 2012 to January 2013, 71 patients with SFA TASC (Trans Atlantic Inter-Societal Consensus)-II B and C occlusive lesions were treated by percutaneous transluminal angioplasty with stenting (30 patients in the Innova group and 41 cases in the Protege group) and were evaluated by retrospective observational data analysis. Chi-square tests for categorical data and time to event provided two-sided p values with a level of significance at 0.05 and 95% confidence intervals (CIs). Survival curves for primary patency were plotted using the Kaplan-Meier method. Univariate analysis for diabetes, hypercholesterolemia, smoking, hypertension, and critical limb ischemia was performed according to the Cox proportional hazards model.Result The mean follow-up was 14 months (range 1–18 months). The occlusive lesions treated were ≤15 cm in length. The 12-month primary patency rate was significantly higher in the Protege group (81.5%; 31/38) than the Innova group (43.3%; 13/30; hazard ratio [HR] 3.0; 95% CI: 1.38–6.8; p = 0.005. The secondary patency was similar to the primary comparison data and showed a significant advantage for the Protege stent (HR 2.9; 95% CI: 1.21–6.99; p = 0.01). Univariate analysis demonstrated that diabetes and smoking were significantly related to patency failure in both groups.Conclusions SFA stenting is generally a safe procedure, but the effectiveness and patency rates are significantly lower for Innova than Protege. Furthermore, preoperative diabetes and smoking continue to be associated with low primary patency rate. These preliminary data suggest that Innova stent is not the treatment of choice for SFA lesions.
Keywords: femoropopliteal lesions; self-expanding bare metal stent system; endovascular interventions; restenosis factors